2016 IEEE International Conference on Robotics and Automation (ICRA) 2016
DOI: 10.1109/icra.2016.7487360
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic modeling and singularity treatment of steerable wheeled mobile robots with joint acceleration limits

Abstract: Non-holonomic omnidirectional mobile robots have higher load carrying capacity than their holonomic counterparts. Once the steer joint configuration is initialized, they can perform arbitrarily complex three-dimensional trajectories in the plane of motion and, as such, are more suitable for industrial contexts. However, their kinematic model presents representational and structural singularities, solutions to which must respect actuator performance limits. Recent research efforts have provided either simple re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…1. proper steering coordination [10,58,61,68], 2. avoidance of kinematic and representational singularities [19,20,21,24,30,60,64,68], 3. fulfillment of steer joint performance limits [11,18,22,50,51,52,53,60,63].…”
Section: Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…1. proper steering coordination [10,58,61,68], 2. avoidance of kinematic and representational singularities [19,20,21,24,30,60,64,68], 3. fulfillment of steer joint performance limits [11,18,22,50,51,52,53,60,63].…”
Section: Mobilitymentioning
confidence: 99%
“…In a first work [63], we present a numeric treatment of SWMR kinematic singularities and a benchmark test trajectory for evaluating the performance of any SMWR controller with respect to these singularities. We also show that our approach outperforms the embedded controller of the BAZAR base (Neobotix-MPO700) in addressing the singularities.…”
Section: Addressing Kinematic Singularities and Motion Discontinuitiesmentioning
confidence: 99%
“…where d and r w denote the wheel offset and radius respectively. For more details about the framework and the kinematic model, the reader is referred to [23], [24], [29].…”
Section: Steerable Mobile Robot Controllermentioning
confidence: 99%
“…The kinematic model presented in this section (detailed in previous work by the authors [10]) is inspired by the pioneer work of Muir [11], Campion [12], Betourne [13] and Low et al [14]. The schematic of a SWMR is shown in Fig.…”
Section: Kinematic Modelmentioning
confidence: 99%
“…at the ground contact point o ci (expressed in the wheel frame F wi ), with v ti and v ni respectively the i th tangential and normal velocities, it can be shown that [10]:…”
Section: A Cartesian Space 3d Model Formulationmentioning
confidence: 99%